Assessing particulate matter concentration level and its limit exceedance based on year-round field measurements of different laying hen building systems. (February 2023) - Li, Zongyang; Xiong, Yijie; Wang, Shaojie; Wang, Chaoyuan; Ji, Boyu; Liu, Yu; Liang, Chao; Tong, Qin
Abstract : Inhaling particulate matter (PM) poses a potential risk on the health of workers and chickens for long-term exposure to highly contaminated air in buildings, while the exceedance of PM concentration limit is still unclear for lack of direct measurement data covering the annual production cycle of laying hen farms. This research investigated the indoor PM characteristics in three typical laying hen building systems of natural mating colony cage (NM), conventional cage (CC), and aviary (AV) in China based on a year-round field measurement of PM concentrations using the Internet of Things. Results suggested that the average PM2.5 and total suspended particulate (TSP) concentrations in NM were 0.042 ± 0.016 and 0.345 ± 0.143 mg m −3, respectively. The corresponding results were 0.048 ± 0.021 and 0.305 ± 0.171 mg m −3 in CC, 0.025 ± 0.012 and 0.786 ± 0.875 mg m −3 in AV, respectively. During the working period, PM2.5 concentrations in 3% and 6.5% of the monitored days exceeded the threshold of 0.075 mg m −3 in NM and CC, meanwhile about 11% of the daily mean TSP concentrations in AV were higher than the recommended limit of 2.4 mg m −3 . Generally, the average PM concentrations in three building systems with appropriate system designs and management were maintained at relatively low levels, which were beneficial to the health and production performance of laying hens. Occasional exceedance of PM concentration thresholds may chronically impair the respiratory health of the workers, and preventive measures should be therefore taken while working in laying hen houses. Highlights: An IoT system was developed to long-term monitor PM concentration in poultry houses. The PM2.5 and TSP concentrations of laying hen building systems in China were low. Occasional exceedances of PM concentration limit were found during working period. The PM exposure risk on the respiratory health existed but lower than other systems.